2013
DOI: 10.1371/journal.pone.0076382
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactor Analysis of Fungal and Bacterial Community Structure in the Root Microbiome of Mature Populus deltoides Trees

Abstract: Bacterial and fungal communities associated with plant roots are central to the host health, survival and growth. However, a robust understanding of the root-microbiome and the factors that drive host associated microbial community structure have remained elusive, especially in mature perennial plants from natural settings. Here, we investigated relationships of bacterial and fungal communities in the rhizosphere and root endosphere of the riparian tree species Populus deltoides, and the influence of soil para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
214
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(256 citation statements)
references
References 61 publications
31
214
0
6
Order By: Relevance
“…Likewise, there was an increased abundance of Anaerolineae (Chloroflexi), Clostridia (Firmicutes), and a subpopulation of Actinobacteria (Saccharothrix spp., unclassified Actinosynnemataceae) in R plants under paddy and upland conditions. In another study, Shakya et al (2013) showed that a high percentage (more than 90%) of operational taxonomic units (OTUs) specific to sampled mature Populus deltoides trees from two watersheds of North Carolina and Tennessee in two seasons (spring and fall) had the dominant phyla Proteobacteria (56.1%), Actinobacteria (17.5%), and Acidobacteria (10%). However, dominance of Proteobacteria was replaced by Actinobacteria from spring to fall in the Tennessee samples.…”
Section: Determination Of Microbiome By Host Host Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, there was an increased abundance of Anaerolineae (Chloroflexi), Clostridia (Firmicutes), and a subpopulation of Actinobacteria (Saccharothrix spp., unclassified Actinosynnemataceae) in R plants under paddy and upland conditions. In another study, Shakya et al (2013) showed that a high percentage (more than 90%) of operational taxonomic units (OTUs) specific to sampled mature Populus deltoides trees from two watersheds of North Carolina and Tennessee in two seasons (spring and fall) had the dominant phyla Proteobacteria (56.1%), Actinobacteria (17.5%), and Acidobacteria (10%). However, dominance of Proteobacteria was replaced by Actinobacteria from spring to fall in the Tennessee samples.…”
Section: Determination Of Microbiome By Host Host Genotypementioning
confidence: 99%
“…This study did not directly explain any host-specific variance in rhizospheric bacterial community structure, instead postulating an indirect influence of changing soil properties (through rhizodeposits and exudates) that showed statistically significant influence on the rhizospheric microbiome. These studies (Ikeda et al, 2011;Shakya et al, 2013) still pose open-ended questions. What are the specific genes/alleles that control microbial communities?…”
Section: Determination Of Microbiome By Host Host Genotypementioning
confidence: 99%
“…Recent studies have used high-throughput sequencing to provide new insights into the bacterial composition and organization of different plant microbiomes, including Arabidopsis, Populus, and maize (9)(10)(11)(12)(13)(14). Detailed characterization of the core root microbiome of Arabidopsis (9)(10)(11) showed that the dominant phyla inside the root (the endosphere) are much less diverse than the phyla in the soil around the root (the rhizosphere), and a potential core root microbiome could be identified.…”
mentioning
confidence: 99%
“…A recent study in maize examined microbiome variation across many different inbred lines at different sites and found a large variation arising from geographical location between three different states in the United States and a relatively smaller dependence on the genotype (12). Although the microbiomes examined in the maize study consisted of combined rhizospheric and endospheric microbes (12), a study in poplar found that the variation between locations in two different states affected both rhizospheric and endospheric microbes (14).…”
mentioning
confidence: 99%
“…Actinomycetes and pseudomonads represent two of the major groups of bacteria found in soils and rhizospheres (16,17) and are likely to simultaneously utilize similar resources, such as iron, or even to compete for them. Both groups produce siderophores to take up this essential element, but different types of molecules are produced by the two groups.…”
mentioning
confidence: 99%